Manajemen Kurikulum Muatan Lokal dalam Pengembangkan Kemampuan Baca Tulis Al Qur’an - Irmalia Putri; Zahrotun Ni’mah Afif (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2024)
This research analyzes the planning, organization, implementation and evaluation of local content curriculum management in developing Al-Qur'an reading and writing skills at SMPN 2 Diwek. The method used is descriptive qualitative, with data collected through observation, interviews and documentation. The results show that the curriculum was initially designed with an administrative model, but was later changed to a grass-roots model due to input from supervisors. Planning is done by preparing a learning plan at the beginning of the semester and submitting it to the school for monitoring. Organizing is carried out by the deputy principal by arranging teaching hours and lesson schedules. Implementation according to the predetermined schedule. Learning includes reading 2 Juz of the Qur'an per semester, recitation knowledge, and short surah imlak. Evaluation involves summative examinations tailored to the Learning Objectives, as well as teaching supervision by the principal and a team of senior teachers